International Trade and Stable Resolutions of Resource Disputes - Michelle R. Garfinkel; Constantinos Syropoulos (Center for Economic Studies and ifo Institute (CESifo), 2022)
We consider a dynamic setting in which two sovereign states with overlapping ownership claims on a resource/asset first arm and then choose whether to resolve their dispute violently through war or peacefully through settlement. Both approaches depend on the states' military capacities, but have very different outcomes. War precludes the possibility of international trade and can be destructive; however, once a winner is declared, arming is unnecessary in future periods. By contrast, a peaceful resolution avoids destruction and supports mutually advantageous trade; yet, settlements must be renegotiated in the shadow of arming and the threat of war. In this setting, we characterize the conditions under which peace arises as a stable equilibrium over time. We find that, depending on the destructiveness of war, time preferences, and the initial distribution of resource endowments, greater gains from trade can reduce arming and pacify international tensions. Even when the gains from trade are relatively small, peace might be sustainable, but only for more uneven endowment distributions.
Keywords: C72; C78; D30; D70; D74; F10; F51; F60; 330; interstate war; armed peace; unarmed peace; security policies; gains from trade; shadow of the future